### (0) Obligation:

Runtime Complexity TRS:
The TRS R consists of the following rules:

le(0, y) → true
le(s(x), 0) → false
le(s(x), s(y)) → le(x, y)
zero(0) → true
zero(s(x)) → false
id(0) → 0
id(s(x)) → s(id(x))
minus(x, 0) → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Rewrite Strategy: FULL

### (1) DecreasingLoopProof (EQUIVALENT transformation)

The following loop(s) give(s) rise to the lower bound Ω(n1):
The rewrite sequence
le(s(x), s(y)) →+ le(x, y)
gives rise to a decreasing loop by considering the right hand sides subterm at position [].
The pumping substitution is [x / s(x), y / s(y)].
The result substitution is [ ].

### (3) RenamingProof (EQUIVALENT transformation)

Renamed function symbols to avoid clashes with predefined symbol.

### (4) Obligation:

Runtime Complexity Relative TRS:
The TRS R consists of the following rules:

le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

S is empty.
Rewrite Strategy: FULL

Infered types.

### (6) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

### (7) OrderProof (LOWER BOUND(ID) transformation)

Heuristically decided to analyse the following defined symbols:
le, id, minus, mod

They will be analysed ascendingly in the following order:
le < mod
id < mod
minus < mod

### (8) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
le, id, minus, mod

They will be analysed ascendingly in the following order:
le < mod
id < mod
minus < mod

### (9) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

Induction Base:
le(gen_0':s3_0(0), gen_0':s3_0(0)) →RΩ(1)
true

Induction Step:
le(gen_0':s3_0(+(n5_0, 1)), gen_0':s3_0(+(n5_0, 1))) →RΩ(1)
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) →IH
true

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (11) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
id, minus, mod

They will be analysed ascendingly in the following order:
id < mod
minus < mod

### (12) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)

Induction Base:
id(gen_0':s3_0(0)) →RΩ(1)
0'

Induction Step:
id(gen_0':s3_0(+(n312_0, 1))) →RΩ(1)
s(id(gen_0':s3_0(n312_0))) →IH
s(gen_0':s3_0(c313_0))

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (14) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
minus, mod

They will be analysed ascendingly in the following order:
minus < mod

### (15) RewriteLemmaProof (LOWER BOUND(ID) transformation)

Proved the following rewrite lemma:
minus(gen_0':s3_0(n526_0), gen_0':s3_0(n526_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n5260)

Induction Base:
minus(gen_0':s3_0(0), gen_0':s3_0(0)) →RΩ(1)
gen_0':s3_0(0)

Induction Step:
minus(gen_0':s3_0(+(n526_0, 1)), gen_0':s3_0(+(n526_0, 1))) →RΩ(1)
minus(gen_0':s3_0(n526_0), gen_0':s3_0(n526_0)) →IH
gen_0':s3_0(0)

We have rt ∈ Ω(n1) and sz ∈ O(n). Thus, we have ircR ∈ Ω(n).

### (17) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)
minus(gen_0':s3_0(n526_0), gen_0':s3_0(n526_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n5260)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

The following defined symbols remain to be analysed:
mod

### (18) NoRewriteLemmaProof (LOWER BOUND(ID) transformation)

Could not prove a rewrite lemma for the defined symbol mod.

### (19) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)
minus(gen_0':s3_0(n526_0), gen_0':s3_0(n526_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n5260)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (20) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

### (22) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)
minus(gen_0':s3_0(n526_0), gen_0':s3_0(n526_0)) → gen_0':s3_0(0), rt ∈ Ω(1 + n5260)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (23) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

### (25) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)
id(gen_0':s3_0(n312_0)) → gen_0':s3_0(n312_0), rt ∈ Ω(1 + n3120)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (26) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

### (28) Obligation:

TRS:
Rules:
le(0', y) → true
le(s(x), 0') → false
le(s(x), s(y)) → le(x, y)
zero(0') → true
zero(s(x)) → false
id(0') → 0'
id(s(x)) → s(id(x))
minus(x, 0') → x
minus(s(x), s(y)) → minus(x, y)
mod(x, y) → if_mod(zero(x), zero(y), le(y, x), id(x), id(y))
if_mod(true, b1, b2, x, y) → 0'
if_mod(false, b1, b2, x, y) → if2(b1, b2, x, y)
if2(true, b2, x, y) → 0'
if2(false, b2, x, y) → if3(b2, x, y)
if3(true, x, y) → mod(minus(x, y), s(y))
if3(false, x, y) → x

Types:
le :: 0':s → 0':s → true:false
0' :: 0':s
true :: true:false
s :: 0':s → 0':s
false :: true:false
zero :: 0':s → true:false
id :: 0':s → 0':s
minus :: 0':s → 0':s → 0':s
mod :: 0':s → 0':s → 0':s
if_mod :: true:false → true:false → true:false → 0':s → 0':s → 0':s
if2 :: true:false → true:false → 0':s → 0':s → 0':s
if3 :: true:false → 0':s → 0':s → 0':s
hole_true:false1_0 :: true:false
hole_0':s2_0 :: 0':s
gen_0':s3_0 :: Nat → 0':s

Lemmas:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)

Generator Equations:
gen_0':s3_0(0) ⇔ 0'
gen_0':s3_0(+(x, 1)) ⇔ s(gen_0':s3_0(x))

No more defined symbols left to analyse.

### (29) LowerBoundsProof (EQUIVALENT transformation)

The lowerbound Ω(n1) was proven with the following lemma:
le(gen_0':s3_0(n5_0), gen_0':s3_0(n5_0)) → true, rt ∈ Ω(1 + n50)